1990
DOI: 10.1084/jem.171.6.2153
|View full text |Cite
|
Sign up to set email alerts
|

Helper T cell-dependent human B cell differentiation mediated by a mycoplasmal superantigen bridge.

Abstract: mAbs recognizing TCR V gene products have helped to define a unique group of potent T cell activators termed superantigens (1). Recognized superantigens include murine selfantigens (2, 3) and a group ofmicrobial toxins, the staphylococcal enterotoxins (SE) (1), and a soluble product ofMycoplasma arthritidis mitogen (MAM) (4). Superantigens share a number of intriguing characteristics. For example, superantigen recognition is almost entirely a function of TCR V a gene usage (1, 2).In addition, superantigens bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…Nonlinked Id-driven B cell autoimmunity resembles the T celldriven autoimmune B cell responses observed with presentation of MHC alloantigens (46,47), viruses (48), superantigens (19,49), or B cells pulsed with synthetic peptide (50,51). In these cases, T-B collaboration is nonlinked in the sense that the B and T cell epitopes do not derive from the same Ag.…”
Section: Discussionmentioning
confidence: 99%
“…Nonlinked Id-driven B cell autoimmunity resembles the T celldriven autoimmune B cell responses observed with presentation of MHC alloantigens (46,47), viruses (48), superantigens (19,49), or B cells pulsed with synthetic peptide (50,51). In these cases, T-B collaboration is nonlinked in the sense that the B and T cell epitopes do not derive from the same Ag.…”
Section: Discussionmentioning
confidence: 99%
“…We co-cultured purified B cells with + -irradiated SEB-reactive CD4 T helper cells in the presence or absence of superantigen. This superantigen-facilitated cognate T-B interaction represents a potent and physiological stimulus [25,26]. We found that stimulation of c-Rel(−/−) B cells with SEB-reactive Th cells in the presence of SEB resulted in a response that was only 25 % of that of the wildtype (Fig.…”
Section: Dna-synthesis (Proliferative) Defects Are Evident In C-rel(−mentioning
confidence: 95%
“…T cell line cells derived from 2 normal donors were used. After 10 days, cultures were terminated and supernatants were assayed for total IgM production by enzyme-linked immunosorbent assay, as described previously (60).…”
Section: Microbial Superantigens As Mediators Of Gvh-like Diseasementioning
confidence: 99%